Akuntansi Murabahah pada Pembiayaan Modal Usaha pada Bank Syariah Indonesia (BSI) Kantor Cabang Pembantu (KCP) Lumajang - Nur Chatib, Novi Dian; Yuliarti, Norita Citra; Nastiti, Ari Sita (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
In the financial sphere that applies the Sharia accounting system, namely Sharia Banks. The existence of Sharia Banks is followed by Islamic Sharia guidelines in their operations, in response to the need for a strong and stable financial transaction framework, with supervision of financial transactions in accordance with Sharia principles. This research aims to identify the implementation of murabahah accounting in the costs of administering business capital at Bank Syariah Indonesia (BSI) KCP Lumajang and also to evaluate the extent to which murabahah accounting is implemented in business capital financing at Bank Syariah Indonesia (BSI) KCP Lumajang according to PSAK No. 102. This research adopts a qualitative strategy and focuses on analyzing the implementation of murabahah accounting in the business capital financing of Sharia Bank (BSI) KCP Lumajang. Sharia Bank (BSI) KCP Lumajang is the subject and location of the research. The materials used are primary and secondary data. The qualitative descriptive analysis method was used to answer the research questions, with the researcher providing a detailed description of the implementation of murabahah accounting in business capital financing at Bank Syariah (BSI) KCP Lumajang. The data obtained proves that the application of murabahah accounting in business capital financing at Bank Syariah Indonesia (BSI) KCP Lumajang involves aspects of recognition, measurement, presentation and disclosure in financial reports. The conclusion is that overall, the implementation of murabahah accounting in business capital financing at Bank Syariah Indonesia (BSI) KCP Lumajang complies with the rules of PSAK No.102. Keywords: Murabahah Accounting, Business Capital Financing, and PSAK No. 102.